The Utilization of Audio-Visual Learning Media in Learning Islamic Cultural History for Grade 10 High School Students - Wadza Umi Rosida; Hafidz (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2024)
Education in Indonesia has always adapted well to keep up with increasingly advanced and developing times, one of which is the implementation of the Merdeka curriculum which aims to improve the quality of student learning through school innovation design. Therefore, this research was initiated to evaluate and identify the effectiveness of school innovation efforts in teaching the History of Islamic Culture to grade 10 high school students through audio-visual learning media. This research uses descriptive qualitative data analysis. The research subjects were students in class 10.3 of SMA Muhammadiyah 2 Surakarta. Data was collected through interviews, field observations, and posttest results conducted over 4 weeks. The results of the research show that the use of audio-visual learning media in learning the History of Islamic Culture for grade 10 students is proven to be able to achieve learning objectives well. This is proven by the post-test answers which show 84% of students answered 10 questions perfectly. The conclusion is that audio-visual learning media is effective in supporting the learning of Islamic Cultural History